Conformational analysis of a modified RGD adhesive sequence. (23rd November 2016) - Triguero, Jordi; Zanuy, David; Alemán, Carlos
Abstract : The conformational preferences of the Arg‐GlE‐Asp sequence, where GlE is an engineered amino acid bearing a 3, 4‐ethylenedioxythiophene (EDOT) ring as side group, have been determined combining density functional theory calculations with a well‐established conformational search strategy. Although the Arg‐GlE‐Asp sequence was designed to prepare a conducting polymer–peptide conjugate with excellent electrochemical and bioadhesive properties, the behavior of such hybrid material as adhesive biointerface is improvable. Results obtained in this work prove that the bioactive characteristics of the parent Arg‐Gly‐Asp sequence become unstable in Arg‐GlE‐Asp because of both the steric hindrance caused by the EDOT side group and the repulsive interactions between the oxygen atoms belonging to the backbone amide groups and the EDOT side group. Detailed analyses of the conformational preferences identified in this work have been used to re‐engineer the Arg‐GlE‐Asp sequence for the future development of a new electroactive conjugate with improved bioadhesive properties. The preparation of this new conjugate is in progress. Copyright © 2016 European Peptide Society and John Wiley & Sons, Ltd. Abstract : The conformational preferences of the Arg‐GlE‐Asp sequence, where GlE is an engineered residue bearing a 3, 4‐ethylenedioxythiophene ring as side group, have been examined.